Managing Financial Crises : The Experience in East Asia - Lane, Timothy; Bulir, Ales.; Hamann, A.; Schulze-Gattas, Marianne (Washington, D.C. : International Monetary Fund, 2000)
The Asian financial crisis of 1997-98 was one of the most dramatic economic events of recent times, which raised many questions regarding the appropriate policy response to financial crises. This paper reviews the experience of this crisis, focusing on the overall strategy of crisis management and the way that strategy was implemented, including with regard to official and private financing, structural reforms, and monetary and fiscal policies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet